Young-of-the-year fish as a prospective bioindicator for aquatic environmental contamination monitoring - Cerveny, Daniel; Turek, Jan; Grabic, Roman; Golovko, Oksana; Koba, Olga; Fedorova, Ganna; Grabicova, Katerina; Zlabek, Vladimir; Randak, Tomas (Water research, 2016)
Toxic metals (Hg, Cd, Pb) and fifteen perfluoroalkyl substances (PFASs) were determined in different fish samples at two locations on the Elbe River in the Czech Republic. The muscle tissue of the two adult fish species most commonly used as bioindicators in central Europe and whole body homogenates of various species of young-of-the-year (YOY) fish were used. The purpose of this study was to evaluate the potential to replace adult fish muscle tissue with YOY fish for contamination monitoring. All of the toxic metals and five of the fifteen PFASs were found in the YOY fish samples while only mercury and PFOS were detected in the muscle tissue of adults. The concentration of total mercury (THg) in the YOY fish homogenates ranged between 0.014 and 0.062 μg g(-1). Of the spectrum of analysed pollutants, only the THg concentrations were lower in YOY fish homogenates than in adult muscle tissue. The cadmium concentration varied from 0.004 to 0.024 μg g(-1) and the lead concentration varied from 0.032 to 0.396 μg g(-1) in YOY fish homogenates, while in most of the adult samples, Cd and Pb were below the detection limit of the analytical methods employed. The PFOS concentrations in YOY fish homogenates were comparable to the concentrations frequently found in adult liver tissue. These results show that mixed shoals of YOY fish can be successfully used for aquatic bio-monitoring. Interspecific variability in the concentrations of the target pollutants in YOY fish whole body homogenates is usually lower than the intraspecific variability of the concentrations of the pollutants in adult fish muscle. YOY fish were found to be a suitable bioindicator and have several advantages compared to adult fish.
Keywords: Animals; rtuť; Mercury; zvířata; prospektivní studie; Fishes; chemické látky znečišťující vodu; Prospective Studies; Water Pollutants, Chemical; Environmental Monitoring; monitorování životního prostředí; ryby